Influence of plate material and screw design on stiffness and ultimate load of locked plating in osteoporotic proximal humeral fractures. Issue 3 (March 2016) - Katthagen, Jan Christoph; Schwarze, Michael; Warnhoff, Mara; Voigt, Christine; Hurschler, Christof; Lill, Helmut
Abstract: Introduction: The main purpose was to compare the biomechanical properties of a carbon-fibre reinforced polyetheretherketone (CF-PEEK) composite locking plate with pre-existing data of a titanium-alloy plate when used for fixation of an unstable 2-part fracture of the surgical neck of the humerus. The secondary purpose was to compare the mechanical behaviour of locking bolts and conventional locking cancellous screws. Methods: 7 pairs of fresh frozen human humeri were allocated to two equal groups. All specimens were fixed with the CF-PEEK plate. Cancellous screws (PEEK/screw) were compared to locking bolts (PEEK/bolt) for humeral head fixation. Stiffness, fracture gap deflection and ultimate load as well as load before screw perforation of the articular surface were assessed. Results were compared between groups and with pre-existing biomechanical data of a titanium-alloy plate. Results: The CF-PEEK plate featured significantly lower stiffness compared to the titanium-alloy plate ( P < 0.001). In ultimate load testing, 6 out of 14 CF-PEEK plates failed due to irreversible deformation and cracking. No significant difference was observed between results of groups PEEK/screw and PEEK/bolt ( P > 0.05). Discussion: The CF-PEEK plate has more elastic properties and significantly increases movement at the fracture site of an unstable proximal humeral fracture model compared to the commonly used titanium-alloy plate. The screw design however does neither affect the constructs primary mechanical behaviour in the constellation tested nor the load before screw perforation.